MENDEKONSTRUKSI MITOS ANAK JALANAN DALAM FILM CAPERNAUM KARYA NADINE LABAKI (KAJIAN SEMIOTIKA ROLAND BARTHES) - Shofwatul Maulidah Ridwan; Rohanda Rohanda; Muhammad Abdul Halim (Universitas Islam Negeri Sumatera Utara Medan, 2026)
This study aims to analyze how the representation of street children and social conditions are constructed as mythical signs in Nadine Labaki's film Capernaum. Employing a qualitative approach with Roland Barthes' semiotic method, this research examines signs at three levels: denotation, connotation, and myth. The results show that the representation of street children, embodied by the character Zain, is shaped through visuals of poverty, neglect, and violence, which at the connotative level signify street children as victims of social structures. This process naturalizes the myth that street children are symbols of the failure of the state and society to protect children's rights. In addition, social conditions such as poverty, injustice, and child neglect are constructed as mythical signs through visual repetition, realistic narratives, and representations of absent state institutions. The film Capernaum ultimately constructs a myth about structural injustice that is considered a “natural” condition in marginalized communities. This study emphasizes that film is not only a medium of entertainment, but also an arena for the production of meaning that is capable of constructing social reality through the mechanism of signs.